Development of knowledge and reported use of sport science by elite New Zealand Olympic class sailors - Mackie, H. W.; Legg, S. J. (Journal of Physiological Anthropology, 1999)
The objective of this study was to determine the change in elite dinghy sailor`s knowledge and use of sport science, three years after the adoption of a sport science support (SSS) programme by Yachting New Zealand for its elite dinghy sailors. A questionnaire was administered to 28 (22 male, six female) elite sailors in April 1994 and to 33 (24 male and nine female) in March 1997 during a training camp for elite sailors. 15 of the sailors participated in 1994 and 1997. The questionnaire asked whether or not the sailors used a training race diary and inquired about their knowledge and use of sport science in the areas of nutrition, psychology and physical conditioning. In 1997, additional questions enquired about sailor`s perception of sport science and its affect on their racing performance. Between April 1994 and March 1997, sailors received sport science support in nutrition, psychology and physical conditioning. Sailors reported a greater amount of fluid drunk on a four-hour sail in 1997 than in 1994 and a greater proportion of sailors ate a high carbohydrate meal after a race in 1997 than in 1994. In 1997, sailors reported feeling less anxiety before a race, and the sailors common to 1994 and 1997 reported feeling less sick before a race in 1997 than in 1994. Increases were observed in volume and intensity of physical training, and improvements were noticed in the chosen type of aerobic training in 1997. Most sailors believed that their knowledge and use of sport science has increased and that their increased use of sport science has led to improvements in racing performance. The results suggest that elite New Zealand sailors` use of sport science improved in the areas of nutrition, sports psychology and physical conditioning between 1994 and 1997. However, when the results were compared with those of Legg and Mackie (1999), it was evident that greater physical conditioning improvements had occurred between 1994 and 1995 than had been sustained since, while the majority of sailor`s sport psychology improvements occurred between 1995 and 1997. Sailors reported fluid intake between 1994 and 1997 had steadily improved. The reason for sailor`s change in emphasis on different areas of sport science over time may be a result of their adopting ideas with which they were most familiar (physical conditioning and nutrition) first, and then adopting the less widely understood discipline of sport psychology once they felt that they had mastered their use of physical conditioning and nutrition. This study indicates that sailors are beginning to understand the importance of personal preparation using sport science principles.